Changes in fasting bile acid profiles after Roux-en-Y gastric bypass and sleeve gastrectomy. Issue 3 (22nd January 2021) - Zhang, Chunlan; Zhang, Jingjing; Zhou, Zhiguang
Abstract: Background: Bile acid is an essential factor that plays a role in metabolic regulation, but how bile acid is regulated after Roux-en-Y gastric bypass (RYGB) and sleeve gastrectomy (SG) remains unclear. This meta-analysis aimed to investigate changes in the levels of fasting bile acids following RYGB and SG. Methods: A systematic literature search of the PubMed, EMBASE, Cochrane Library and Web of Science databases through July 2020 was performed in accordance with the Meta-analysis Of Observational Studies in Epidemiology (MOOSE) guidelines and Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) statement. The concentrations of bile acids were evaluated. Results: Thirteen studies with 289 patients were included. Our results showed that patients who underwent RYGB had increased levels of fasting total bile acids, primary bile acids, secondary bile acids, conjugated bile acids, and unconjugated bile acids, but no significant differences in all these bile acid levels were observed in patients who underwent SG. Furthermore, 12a-hydroxylated bile acid levels and the 12a-hydroxylated/non-12a-hydroxylated bile acid ratio also increased following RYGB. Conclusion: In this study, we found that fasting bile acid levels, especially 12a-hydroxylated bile acids levels, were increased after RYGB. However, no differences in fasting bile acid levels were observed following SG. Abstract : Supplemental Digital Content is available in the text